Compliance age: The importance of the integrity program in business relationships - Argentina , Pedro Henrique Hernandes; Filho, Gilberto Ferreira Marchetti (Seven Editora, 2023)
Compliance culture has become a reality among companies in Brazil. Whereas in the past the program existed only for "English eyes only", today, institutions structure and implement the integrity program so that it effectively meets the expectations of the legal entity, characterized as a set of rules, mechanisms and tools that operate in the prevention, detection and remediation of illegal conduct, as well as negative behaviors that could harm the company. The compliance program began to have greater relevance with the scandals of Operation Lava-Jato and the subject was implemented in the Brazilian legislation by means of Law no. 12.846/2013; regulated by Decree no. 11.129/ 2022, which revoked the previous one from the year 2015. In the scenario of globalization and scandals involving big names in the corporate world, the protections that an effective compliance program can provide started to be desired by entrepreneurs; a transaction, either between companies or between companies and people, when not thoroughly observed, may cause irreparable damage to the institution. In this sense, compliance has been highlighted in the corporate scenario. The present work aims at elucidating the importance of a compliance program, as well as highlighting the pillars that constitute an effective program, emphasizing the benefits for the institution. The study was developed in an inductive manner, having as scope bibliographic reviews, among them online academic journals, as well as the use of information already made available in books, articles, legislation, and other published sources. DOI:https://doi.org/10.56238/uniknowindevolp-068